2020
DOI: 10.1556/030.2020.01080
|View full text |Cite
|
Sign up to set email alerts
|

A simplified in vitro model for investigation of the antimicrobial efficacy of various antiseptic agents to prevent peri-implantitis

Abstract: The biofilm formation by oral bacteria on the implant surface is one of the most remarkable factors of peri-implant infections, which may eventually lead to bone resorption and loss of the dental implant. Therefore, the elimination of biofilm is an essential step for the successful therapy of implant-related infections. In this work we created a basic in vitro model to evaluate the antibacterial effect of three widely used antiseptics. Commercially pure (CP4) titanium sample discs with sand blasted, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Peri-implant inflammation and lesions are of multifactorial nature, but it is a fact unequivocally supported by the literature that P. gingivalis plays a leading role in both cases [24,50,51]. In a previous study, it was demonstrated that P. gingivalis has the ability to colonize titanium surface in multiple interconnected layers, forming a biofilm, namely a polysaccharide coat (glycocalyx), which is a protective layer for the bacterial population [52,53].…”
Section: Discussionmentioning
confidence: 95%
“…Peri-implant inflammation and lesions are of multifactorial nature, but it is a fact unequivocally supported by the literature that P. gingivalis plays a leading role in both cases [24,50,51]. In a previous study, it was demonstrated that P. gingivalis has the ability to colonize titanium surface in multiple interconnected layers, forming a biofilm, namely a polysaccharide coat (glycocalyx), which is a protective layer for the bacterial population [52,53].…”
Section: Discussionmentioning
confidence: 95%
“…The antibacterial efficiency of these solutions was proven by our research group previously [ 44 ]. Venkei et al found that 5 min treatment of PVPI and ClO 2 led to significant elimination of Streptococcus mitis and Streptococcus salivarius in their in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ] Additional evidence that the use of chlorine dioxide oral rinses, available OTC in most drug stores or supermarket with other oral care products reduces oral biofilm intraorally and rinsing removable prosthetics (dentures) in this eliminates biofilm decreasing aspiration potential. [ 42 , 43 ] Therefore, placing all elderly patients on chlorhexidine or chlorine dioxide daily rinses as a preventive measure should be recommended to aid in preventing potential aspiration pneumonia. This should be a more predictable approach in elderly patients who lack manual dexterity to perform oral homecare with a toothbrush.…”
Section: Pulmonary Diseasementioning
confidence: 99%